Investıgatıon of The Relatıon Between Moral Sensıtıvıty of Nursıng Students and Occupatıonal Self- Esteem - Demircan B.; Kıyak Yorulmaz Y.; Aştı T. (My University, 2025)
Background: Occupational self-esteem is critical for achieving professional identity in the nursing profession, where human well-being is a central principle. Occupational self-esteem is also directly related to moral sensitivity.Objectives: This study aimed to investigate the association between occupational self-esteem and moral sensitivity among nursing students.Methods: In this descriptive, correlational study, an introductory qualification data form, the Modified Moral Sensitivity Questionnaire for Student Nurses, and the Occupational Self-Esteem Scale were used. The sample comprised second-, third-, and fourth-year nursing students (n=171) from a foundation university in Istanbul, Turkey. The study included 161 nursing students who agreed to participate.Results: The students\" average total moral sensitivity score was 5.03±0.58. Significant variation (p=.001) between the genders was observed in the mean scores from the Expertise Knowledge Enrollment subscale, as well as among nurses in their communication of distress with friends (p=.034), and in the Interpersonal Orientation subscale among those who voluntarily chose nursing as their field of study (p=.033). The mean total occupational self-esteem score was 116.27±17.72. Significant variation was observed among the scores related to class level (p=.004), taking ethics courses (p=.002), choosing the nursing department voluntarily (p=.001), satisfaction with being a nursing student (p=.001), encountering ethical dilemmas (p=.013), and having knowledge about occupational self-concept (p=.002). A statistically significant but weakly positive correlation (r=.18; p=.021) was found between occupational self-esteem and moral sensitivity.Conclusion: There was a weak but positive relationship between occupational self-esteem and moral sensitivity among nursing students. Therefore, integrating the concepts of occupational self-esteem and ethical values is necessary to achieve occupational autonomy in nursing education.Keywords:Nursing students,moral sensitivity,occupational self-esteem
Keywords: Hemşirelik; Sağlık Bilimleri; Nursing; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing